EVALUASI WEBSITE MONITORING SKUTER LISTRIK SEWA BERBASIS IOT DENGAN PROTOKOL MQTT - Revikasari, Yovi; Pramaita, Nyoman; Elba Duta Nugraha, I Putu (Jurnal SPEKTRUM; Vol 11 No 3 (2024): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2024.v11.i03.p6, 2024)
This research aims to evaluate the implementation and testing of an Internet of Things (IoT)-based electric scooter rental monitoring system using the MQTT protocol. The monitoring system is designed to track the location and condition of electric scooters through a website integrated with IoT devices. Data such as speed, GPS location, and the status of the help button are transmitted from the scooter to the website via the MQTT protocol. Testing was conducted using the blackbox method to evaluate the system's functionality, and a User Experience (UX) analysis was performed to assess user satisfaction with the website interface. The blackbox testing results showed that the system successfully processed and displayed data as expected, with reliable MQTT communication that effectively transmitted data without loss or delay. Additionally, the UX evaluation involving 30 respondents yielded an average score of 4.57 out of 5. The respondents' assessment indicated that the website interface is easy to use and features a user-friendly visual design .